Effect of Food on the Pharmacokinetics of Fluoxetine in Healthy Male Adult Volunteers(Conference Paper )# - Al-Tamimi, Duaa; Al-Kinani, Khalid; Taher, Salam; Hussein, Ahmed (Iraqi Journal of Pharmaceutical Sciences, 2023)
Fluoxetine (FX) is an antidepressant drug administered only orally in humans. Despite the wide use of FX, until now, there is only limited literature concerning the pharmacokinetics (PK) of FX and the effect of food on its PK. Thus, the objective of this investigation was to study the PK of FX in Arabic healthy male adult volunteers under fasting and fed conditions. In the fasting study, FX 20 mg capsules (Prozac®, Eli Lilly, Canada) were administered to 41 volunteers after overnight fasting of 12 hours, followed by blood sampling from each volunteer immediately before dosing (zero time) and then at 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 24, 36, 48, 60, 72, 96, 120, and eventually at 144 hours after FX dosing. The fed study was conducted after 90 days wash-out period following the completion of the fasting study. The same subjects who received FX in the fasting study were administered the drug directly after a fatty breakfast (fed study), followed by blood sampling intervals similar to the schedule mentioned above for the fasting study. The current investigation demonstrated no statistical differences in the FX pharmacokinetic parameters Cmax, AUC0–t, AUC0–∞, Kel, T1/2, MRT, Cl/F, and Vd/F after fasting compared to the fed conditions, whereas there was statistically significant elongation in the Tmax values after food intake. Therefore, this study concludes the absence of food effect on the PK of FX (except Tmax) in the Arabic population and confirms the method of administration mentioned in the product information but also concludes high interindividual variation in FX exposure (AUC), which suggest that therapeutic drug monitoring (TDM) might be advisable when feasible.